Finding market focus for solution business development - Suvi Nenonen; Kaj Storbacka (jbm - Journal of Business Market Management, 2013)
Firms wanting to move towards solution business models increasingly focus on their customers' value-in-use, and often end up redefining their market around what the solution makes possible for the customer. However, all customers do not accept a value-in-use based approach. Hence, a key determinant of success in solution business relates to a firm's ability to identify segments and customers that are best suited for solution business, i.e., to find market focus. In this paper we develop a framework that assists firms to choose the right markets to focus on, and illustrate the use of the framework with two action research case studies. The framework consists of a market picture, describing the broad ambit of a market actor, and market arenas within the market picture, selected based on morphological analysis. The case studies illustrate how the framework helped managers to escape the market myopia experienced by firms with established market definitions.
urn:nbn:de:0114-jbm-v6i3.455
Keywords: 650; Solution Business; Market; Market Definition; Morphological Analysis